Influência do capital social online na qualidade de vida relacionada à saúde bucal de adolescentes - Borstmann, Eduarda da Silveira (2024)
Oral diseases remain highly prevalent, causing numerous impacts on people's lives. Among the determinants of oral health, social determinants have been highlighted, as they influence outcomes more distally. Within this framework, social capital has been considered one of the key determinants. Several studies have consistently demonstrated associations between levels of social capital and oral health conditions. However, all studies that have sought to investigate this relationship are based on an offline context. While these studies are important, they do not consider the rapid development of the internet and its effects on society, including the formation of online friendship and support networks. Therefore, there is a need for studies to understand and clarify the influence that online social capital can have on oral health-related quality of life (OHRQoL), especially during adolescence, a period in which the internet is frequently used. Thus, the objective of this study was to evaluate the relationships between online social capital and OHRQoL of adolescents in the municipality of Santa Maria, RS, Brazil. This is a cross-sectional study nested within a cohort designed with 639 children who were first assessed in 2010. The same individuals were reassessed in 2012, 2017, and 2020. After 12 years, the adolescents were contacted again. This study only considered data from the 12-year follow-up, in which adolescents were between 14 and 18 years old. OHRQoL was assessed using the short-form Brazilian version of the Child Perception Questionnaire (CPQ 11-14). Online social capital was assessed through the questions "How often do you use social media (e.g., Instagram or WhatsApp) to communicate with friends or family?" and "Are there people you communicate with online (e.g., Instagram or WhatsApp) whom you trust to help you solve your problems?" Offline social capital, demographic, socioeconomic, psychosocial, and clinical variables were also considered as adjustment factors. Adjusted Poisson regression analysis was used to evaluate the relationship between different social capital variables and the overall CPQ11-14 scores. The results were presented as Rate Ratios (RR) and 95% confidence intervals (95% CI). A total of 406 adolescents were assessed. Most adolescents (95,3%) used social media every day or almost every day, and 62.9% reported having someone they could trust online. The mean CPQ11-14 scores were 10.9 (SD 8.1). Adolescents with low levels of online social trust had CPQ11-14 scores 8% higher (RR 1.08; 95% CI 1.01–1.15) than their peers, suggesting a worse OHRQoL. The frequency of social media use was not significantly related to the outcome. It was concluded that online social trust may have positive effects on the subjective oral health of adolescents.